Deuterated Linoleic Acid Attenuates the RBC Storage Lesion in a Mouse Model of Poor RBC Storage - Kim, Christopher Y.; Johnson, Hannah; Peltier, Sandy; Spitalnik, Steven L.; Hod, Eldad A.; Francis, Richard O.; Hudson, Krystalyn E.; Stone, Elizabeth F.; Gordy, Dominique E.; Fu, Xiaoyun; Zimring, James C.; Amireault, Pascal; et al. (Frontiers in Physiology, 2022)
BACKGROUND: Long-chain polyunsaturated fatty acids (PUFAs) are important modulators of red blood cell (RBC) rheology. Dietary PUFAs are readily incorporated into the RBC membrane, improving RBC deformability, fluidity, and hydration. However, enriching the lipid membrane with PUFAs increases the potential for peroxidation in oxidative environments (e.g., refrigerated storage), resulting in membrane damage. Substitution of bis-allylic hydrogens with deuterium ions in PUFAs decreases hydrogen abstraction, thereby inhibiting peroxidation. If lipid peroxidation is a causal factor in the RBC storage lesion, incorporation of deuterated linoleic acid (DLA) into the RBC membrane should decrease lipid peroxidation, thereby improving RBC lifespan, deformability, filterability, and post-transfusion recovery (PTR) after cold storage. STUDY DESIGN AND METHODS: Mice associated with good (C57BL/6J) and poor (FVB) RBC storage quality received diets containing 11,11-D2-LA Ethyl Ester (1.0g/100g diet; DLA) or non-deuterated LA Ethyl Ester (control) for 8 weeks. Deformability, filterability, lipidomics, and lipid peroxidation markers were evaluated in fresh and stored RBCs. RESULTS: DLA was incorporated into RBC membranes in both mouse strains. DLA diet decreased lipid peroxidation (malondialdehyde) by 25.4% and 31% percent in C57 mice and 12.9% and 79.9% in FVB mice before and after cold storage, respectively. In FVB, but not C57 mice, deformability filterability, and PTR were significantly improved. DISCUSSION: In a mouse model of poor RBC storage, with elevated ROS production, DLA attenuated lipid peroxidation and significantly improved RBC storage quality.